(3GdegGQI aj GOGQI GdGReGJ hMd GdeTcdGJ (B:s (3GdGSS GdfXQjI hGdJWHjbjI (B/s - (3MQjR, SGej eMeO gTGes ((3YeGf(B: s (3OGQ GdHOGjI(B, s, 2007)
(3Hjf jOj GdcJGH, bhGYO heQGMd hGfhGY GOGQI GdCReGJ, GOGQI GdCReGJ aj GdGSdGe, GdCSS GdfXQjI GdYGeI dYde GOGQI GdCReGJ, GdCSS GdJWHjbjI GdYGeI dYde GOGQI GdCReGJ, cja JWhQ bOQJc Ydi Md GdeTcdGJ, fgGjI GdeWGas
(3HHdjhZQGajG(B: (3U(B.189-190s
Keywords: (3GOGQIs; (3GdCReGJ GdGbJUGOjIs